Treatment Evaluation of Melasma Patients in Dr. Hasan Sadikin General Hospital Bandung in period of 2013â2014 - Sabila, Ayu Adzani; Hindritiani, Reti; Luftimas, Dimas Erlangga (Althea Medical Journal, 2016)
Background: Melasma is hyperpigmentation of the skin especially located on face exposed to the sunlight. This condition was characterized by brown to gray-brown macula with irregular border. Difficulties in treatment of melasma arise from high tendency for relapse, expensive cost, and high risk of side effects such as erythema, sores, scales, and acne eruption. Study about evaluation of melasma therapy in Dr. Hasan Sadikin General Hospital Bandung have not ever been done before. Therefore, this study was conducted to evaluate therapy of melasma in the Policlinic of Dermatology and Venereology, Dr. Hasan Sadikin General Hospital Bandung.Methods: This study was retrospectively descriptive. Data were obtained from the new melasma patient medical records of Policlinic of Dermatology and Venereology of Dr. Hasan Sadikin General Hospital Bandung in period of January 2013â2014. Sampling method used in this study was total sampling. Treatments of melasma were evaluated by using Melasma Area Severity Index (MASI) score. Collected data were processed and presented in frequency distribution and percentage.Results: The most used topical drugs were combination of hydroquinone and tretinoin, and all of patients received sunblock. Most frequent time interval was two weeks (30.8%). The most common side effect was erythema (10 out of 22). Decreased MASI score was discovered in 48.1% and the most decreased category was mild (14 out of 25). Conclusions: The very common topical drugs used are hydroquinone and tretinoin. The side effect of the treatment is Erythema. The decreased MASI score is mild. [AMJ.2016;3(4):610â5]DOI:Â 10.15850/amj.v3n4.947